Assessment of seed quality and storage methods of farmers' saved cereal seeds in Jhansi district - MUKESH KUMAR; MAYANK KUMAR RAI; SANDEEP KUMAR LAL (Seed Research, 2026)
A survey was conducted during 2008 to assess the seed quality and storage methods followed by famers in Jhansi district of Uttar Pradesh. The seed samples of cereal crops representing the routine cropping pattern practiced by the farmers viz., wheat and maize were collected from 51 rural households of nine villages, namely Baratha, Kochhabhnabar, Karnguwanji, Parichha, Karari, Padari, Jamaura, Jauhari and Chirgnaw located within a range of 30 km of Jhansi district. The seeds stored for sowing purpose were randomly sampled using standard sampling procedures from farm households to estimate the different seed quality parameters. The type of storage method and container was decided on the basis of farmer's requirements, quantity of seed and storage period. The commonly used seed storage methods/ containers included polythene lined urea bag, jute bag, room storage, bunnda, metal container, plastic container and mud pot.